Perspectives on Stem Cell-Based Elastic Matrix Regenerative Therapies for Abdominal Aortic Aneurysms - Bashur, Chris A. (AlphaMed Press, 2013)
Abdominal aortic aneurysms (AAAs) are potentially fatal conditions that are characterized by decreased flexibility of the aortic wall due to proteolytic loss of the structural matrix. This leads to their gradual weakening and ultimate rupture. Drug-based inhibition of proteolytic enzymes may provide a nonsurgical treatment alternative for growing AAAs, although it might at best be sufficient to slow their growth. Regenerative repair of disrupted elastic matrix is required if regression of AAAs to a healthy state is to be achieved. Terminally differentiated adult and diseased vascular cells are poorly capable of affecting such regenerative repair. In this context, stem cells and their smooth muscle cell-like derivatives may represent alternate cell sources for regenerative AAA cell therapies. This article examines the pros and cons of using different autologous stem cell sources for AAA therapy, the requirements they must fulfill to provide therapeutic benefit, and the current progress toward characterizing the cells' ability to synthesize elastin, assemble elastic matrix structures, and influence the regenerative potential of diseased vascular cell types. The article also provides a detailed perspective on the limitations, uncertainties, and challenges that will need to be overcome or circumvented to translate current strategies for stem cell use into clinically viable AAA therapies. These therapies will provide a much needed nonsurgical treatment option for the rapidly growing, high-risk, and vulnerable elderly demographic.